2021
DOI: 10.1016/j.ssmph.2021.100855
|View full text |Cite
|
Sign up to set email alerts
|

Does postponing retirement affect cognitive function? A counterfactual experiment to disentangle life course risk factors

Abstract: Evidence suggests that contemporaneous labor force participation affects cognitive function; however, it is unclear whether it is employment itself or endogenous factors related to individuals’ likelihood of employment that protects against cognitive decline. We exploit innovations in counterfactual causal inference to disentangle the effect of postponing retirement on later-life cognitive function from the effects of other life-course factors. With the U.S. Health and Retirement Study (1996–2014, n = 20,469),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 74 publications
1
24
0
1
Order By: Relevance
“…The association between retirement and functional impairment among women did was not robust. These observations are similar to results from a study in the USA that found differences in the retirement-cognitive decline association between men and women 43 . These findings might be, at least in part, due to women’s commonly low-status jobs and weaker attachment to the job market, particularly in SSA.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The association between retirement and functional impairment among women did was not robust. These observations are similar to results from a study in the USA that found differences in the retirement-cognitive decline association between men and women 43 . These findings might be, at least in part, due to women’s commonly low-status jobs and weaker attachment to the job market, particularly in SSA.…”
Section: Discussionsupporting
confidence: 89%
“…According to Hale et al. 43 , postponed retirement benefits cognitive function across diverse populations. However, our findings are inconsistent with previous studies suggesting better health outcomes during retirement 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…We focused on the overall association between retirement age and cognitive impairment. It is presumed, however, that the consequences of working and retirement on later‐life health and cognition depends on many different individual, occupational and societal factors, 35 such as education, 36 psychosocial working conditions, 37 and the cognitive demands of the job 38,39 . Future research should explore whether there are particular subgroups for whom, or conditions under which, early or later retirement causally affects later‐life cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, multiple epidemiological studies in modern societies suggest that the abrupt loss of regular work-related cognitive stimulus due to retirement results in a parallel increase in the risk of cognitive decline. Even when adjusting for confounders that might explain both early retirement and cognitive decline such as comorbid medical conditions, those that retire earlier appear to experience ARCD sooner [ 11 , 12 , 141 ]. This effect is also greatest in those that have higher levels of education, where at a population level, work-related cognitive demand might be greatest and the decrease in cognitive demand after retirement might be most abrupt [ 140 ].…”
Section: Cognitive Demands Across the Lifespanmentioning
confidence: 99%